Plasmid-mediated sulfonamide resistance in Haemophilus ducreyi. - Albritton, W L (1982)
Clinical isolates of Haemophilus ducreyi from patients with chancroid were shown to have one or more 4.9- to 7.0-megadalton non-self-transferable plasmids and to have in vitro resistance to sulfonamides. Transformation of Escherichia coli to sulfonamide resistance was associated with the acquisition of a 4.9-megadalton plasmid, which did not confer linked resistance to streptomycin. The guanine-plus-cytosine content of this plasmid was found to be 57%. Filter-blot hybridization and restriction endonuclease digestion studies suggested a relationship of this plasmid to RSF1010. Electron microscope heteroduplex analysis confirmed this relationship. The identification in H. ducreyi of a plasmid closely related to plasmids found in enteric species, rather than transposition of a resistance determinant to an indigenous plasmid, suggests that further dissemination of the enteric plasmid pool to this genus is possible since plasmid transfer between certain Haemophilus species is readily demonstrated.